A systematic review of ultrasound biomicroscopy use in pediatric ophthalmology - Alexander, Janet L. (Eye (Lond), 2020)
Ultrasound biomicroscopy (UBM) is the only available option for noninvasive, high-resolution imaging of the intricate iridociliary complex, and for anterior segment imaging with corneal haze or opacity. While these unique features render UBM essential for specific types of trauma, congenital anomalies, and anterior segment tumors, UBM imaging has found clinical utility in a broad spectrum of diseases for structural assessments not limited to the anterior intraocular anatomy, but also for eyelid and orbit anatomy. This imaging tool has a very specific niche in the pediatric population where anterior segment disease can be accompanied by corneal opacity or clouding, and anomalies posterior to the iris may be present. Pediatric patients present additional diagnostic challenges. They are often unable to offer detailed histories or fully cooperate with examination, thus amplifying the need for high-resolution imaging. This purpose of this systematic review is to identify and synthesize the body of literature involving use of UBM to describe, evaluate, diagnose, or optimize treatment of pediatric ocular disease. The collated peer-reviewed research details the utility of this imaging modality, clarifies the structures and diseases most relevant for this tool, and describes quantitative and qualitative features of UBM imaging among pediatric subjects. This summary will include information about the specific applications available to enhance clinical care for pediatric eye disease.